Effect-site concentration of remifentanil required to blunt haemodynamic responses during tracheal intubation: A randomized comparison between single- and double-lumen tubes. Issue 1 (January 2018) - Kim, Tae Kyong; Hong, Deok Man; Lee, Seo Hee; Paik, Hyesun; Min, Se Hee; Seo, Jeong-Hwa; Jung, Chul-Woo; Bahk, Jae-Hyon
Objective: To investigate the effect-site concentration of remifentanil required to blunt haemodynamic responses during tracheal intubation with a single-lumen tube (SLT) or a double-lumen tube (DLT). Methods: Patients scheduled for thoracic surgery requiring one-lung ventilation were randomly allocated to either the SLT or DLT group. All patients received a target-controlled infusion of propofol and a predetermined concentration of remifentanil. Haemodynamic parameters during intubation were recorded. The effect-site concentration of remifentanil was determined using a delayed up-and-down sequential allocation method. Results: A total of 92 patients were enrolled in the study. The effective effect-site concentrations of remifentanil required to blunt haemodynamic responses in 50% of patients (EC50 ) estimated by isotonic regression with bootstrapping was higher in the DLT than the SLT group (8.5 ng/ml [95% confidence interval (CI) 8.0–9.5 ng/ml] versus 6.5 ng/ml [95% CI 5.6–6.7 ng/ml], respectively). Similarly, the effective effect-site concentrations of remifentanil in 95% of patients in the DLT group was higher than the SLT group (9.9 ng/ml [95% CI 9.8–10.0 ng/ml] versus 7.0 ng/ml [95% CI 6.9–7.0 ng/ml], respectively). Conclusions: This study demonstrated that a DLT requires a 30% higher EC50 of remifentanil than does an SLT to blunt haemodynamic responses during tracheal intubation when combined with a target-controlled infusion of propofol. Trial registration: Clinicaltrials.gov identifier: NCT01542099.